Системы энергоснабжения учебное пособие - Крайнов, А. В. специалист в области теплотехники доцент Томского политехнического университета, кандидат физико-математических наук 1974- (Изд-во ТПУ, 2014)
The aim of the study aid is to develop the skills and abilities of use professionally oriented foreign language in heat power engineering with regard to the presentation of its fundamental concepts and laws in the classical form. The combination of domestic and foreign technologies teaching in high schools is implemented in the coursebook. The book is intended for the students of oil and gas business and power energy specialities. The complexity of presentation allows the use the study aid in the frame of joint international educational programs, in the sphere of elite technical education and in advanced training or use it as self-study.